Criminal Liability for the Misappropriation of Authorship from 1830s to Early 20th Century - Žiedė, Ramunė (Teisė, 2021)
This article analyzes the development of criminal liability for the misappropriation of authorship in Lithuania in the period of application of the legal acts of Tsarist Russia from the 1830s until the restoration of Lithuania’s independence in early 20th century. Norms of different periods are being compared with each other, the oldest criminal norm for the misappropriation of authorship is sought and identified. The appendices of the article also present the citation of the norms of misappropriation of authorship in the original (19th century Russian) language and its translation into Lithuanian, as well as a graph depicting norms of misappropriation of authorship, established in different legal acts, their correlation at different times, and the content of the norms in force with each other.